Wave-induced response and fatigue analysis of free-spanning submarine cables with nonlinear bending stiffness - Cai, Ye; Zhu, Degao; Zhang, Shiguan; Li, Xiaojun; Cen, Zhenjin; Qi, Qianshuo; Wang, Zhenkui; Guo, Zhen; Sun, Haiquan (Frontiers in Built Environment, 2026)
IntroductionUnder long-term wave–current interactions, the free-spanning submarine cables are prone to fatigue damage. Owing to the presence of helically wound layers within the submarine cable, its bending stiffness exhibits pronounced nonlinear characteristics, which in turn exert a substantial influence on its dynamic response and fatigue life. Consequently, this study investigates the influence of nonlinear bending stiffness on the wave-induced response and fatigue characteristics of submarine cables.MethodsFirst, a full-scale local finite element model is developed in ABAQUS to derive the nonlinear bending stiffness of the cable, which is validated against theoretical formulations. Subsequently, the slip stiffness, stick stiffness, and nonlinear bending stiffness models are incorporated into OrcaFlex to perform global dynamic analyses under combined wave–current conditions. The effects of the three stiffness models on the cable’s motion response, load transfer characteristics, and fatigue performance are then systematically evaluated.ResultsThe results indicate that the motion and load response of short-span cables are highly sensitive to nonlinear bending stiffness. As the free-span length increases, the system behavior gradually transitions from a bending-dominated regime to a tension-dominated one. Moreover, the lead sheath is the most susceptible to fatigue failure. Compared to the nonlinear bending stiffness model, employing slip stiffness underestimates the fatigue life by 39%, whereas the use of stick stiffness leads to an overestimation of fatigue life by 25%.DiscussionAccounting for nonlinear bending stiffness is crucial for enhancing the long-term operational reliability of free-spanning submarine cables in structural design and fatigue assessment.